On some F - contraction of Piri–Kumam–Dung–type mappings in metric spaces - Jelena Z.Vujaković (University of Defence in Belgrade, 2020)
Introduction/purpose: This paper establishes some new results of Piri– Kumam–Dung-type mappings in a complete metric space.Тhe goal was to improve the already published results. Methods: Using the property of a strictly increasing function as well as the known Lemma formulated in (Radenović et al, 2017), the authors have proved that a Picard sequence is a Cauchy sequence. Results: New results were obtained concerning the F – contraction mappings of S in a complete metric space. To prove it, the authors used only property (W1). Conclusion:The authors believe that the obtained results represent a significant improvement of many known results in the existing literature.